(5b-9)-3(8-2b)=b

Simple and best practice solution for (5b-9)-3(8-2b)=b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5b-9)-3(8-2b)=b equation:


Simplifying
(5b + -9) + -3(8 + -2b) = b

Reorder the terms:
(-9 + 5b) + -3(8 + -2b) = b

Remove parenthesis around (-9 + 5b)
-9 + 5b + -3(8 + -2b) = b
-9 + 5b + (8 * -3 + -2b * -3) = b
-9 + 5b + (-24 + 6b) = b

Reorder the terms:
-9 + -24 + 5b + 6b = b

Combine like terms: -9 + -24 = -33
-33 + 5b + 6b = b

Combine like terms: 5b + 6b = 11b
-33 + 11b = b

Solving
-33 + 11b = b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-1b' to each side of the equation.
-33 + 11b + -1b = b + -1b

Combine like terms: 11b + -1b = 10b
-33 + 10b = b + -1b

Combine like terms: b + -1b = 0
-33 + 10b = 0

Add '33' to each side of the equation.
-33 + 33 + 10b = 0 + 33

Combine like terms: -33 + 33 = 0
0 + 10b = 0 + 33
10b = 0 + 33

Combine like terms: 0 + 33 = 33
10b = 33

Divide each side by '10'.
b = 3.3

Simplifying
b = 3.3

See similar equations:

| i=pod | | -3y-9=6y+27 | | .33(k+15)=2k+2 | | n=2py^3-5px | | 7m+21=35+24m | | 0.2x-0.6666667(x-8)=6x | | 4q+3q-1=5-q | | 7z+10=7(z+3) | | 7+21m=35+24m | | -0.2x=6 | | 8m-5m=9 | | -4(k-1)=4 | | 0.5m=m+10 | | -110+1x+7x=58 | | 2p-9=15g-9 | | 19x+51x-16=10(7x+15) | | a+4=13-2a | | 3(m+1)=-4(-2-m)+2 | | F(n)=150-20n | | 2(3-x)=10 | | xC=S-C | | x+4*2=6x | | w+2=6-w | | 5(x-1)+2(x+2)=34 | | 3y-5y=30 | | 10x-8x+6=x-11 | | 3p+-4=31 | | -11=-2x+1+5x | | 19z+31=26z-74 | | 2(3-y)=4y+9 | | 8w-3a=36 | | (3p-7)+(5p-6)=0 |

Equations solver categories